Respuesta :

Answer:

17 x^2

Step-by-step explanation:

(8x^2 + 8x) – (-9x^2 + 8x)

Distribute the minus sign

8x^2 + 8x + 9x^2 - 8x

Combine like terms

17 x^2 +0x

17x^2

Answer:

17x^2

Step-by-step explanation:

(8x^2 + 8x) – (-9x^2 + 8x) =

The parentheses on the left side are unnecessary, so just remove them.

= 8x^2 + 8x – (-9x^2 + 8x)

To remove the right set of parentheses, distribute the negative sign.

= 8x^2 + 8x + 9x^2 - 8x

Now combine like terms.

= 8x^2 + 9x^2 + 8x - 8x

= 17x^2

ACCESS MORE